2014
DOI: 10.1038/nsmb.2816
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of ligand-dependent alternating access in LeuT

Abstract: The leucine transporter (LeuT) from Aquifex aeolicus is a bacterial homolog of neurotransmitter:sodium symporters (NSS) that catalyze reuptake of neurotransmitters at the synapse. Crystal structures of wild type (WT) and mutants of LeuT have been interpreted as conformational states in the coupled transport cycle. However, the mechanistic identities inferred from these structures have not been validated and the ligand-dependent conformational equilibrium of LeuT has not been defined. Here, we utilized distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
199
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(233 citation statements)
references
References 52 publications
26
199
8
Order By: Relevance
“…This methodology has been successfully applied to define coupled conformational cycles for a number of transporter classes (13,(26)(27)(28)(29)(30)(31)(32). We find that patterns of distance distributions between pairs of spin labels monitoring the intra-and extracellular sides of Mhp1 are consistent with isomerization between the crystallographic inward-and outward-facing conformations.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…This methodology has been successfully applied to define coupled conformational cycles for a number of transporter classes (13,(26)(27)(28)(29)(30)(31)(32). We find that patterns of distance distributions between pairs of spin labels monitoring the intra-and extracellular sides of Mhp1 are consistent with isomerization between the crystallographic inward-and outward-facing conformations.…”
mentioning
confidence: 70%
“…The results presented here describe the ligand-dependent equilibrium between these conformations, reveal that substrate but not Na + binding changes the energetics of these conformations, and indicate that the bundle and scaffold motifs are not strictly rigid bodies. In conjunction with a previous investigation of LeuT (13), this work illuminates commonalities and differences in the structural mechanism of alternating access in the LeuT-fold class of ioncoupled transporters.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The degree of this opening and its direction has been debated ever since, as it probably lifts TM1a into the membrane. Kazmier et al 40 have recently performed measurements between spin-label pairs in LeuT and observed significantly smaller degree of openings of the IF vestibule for WT LeuT compared to the IFo crystal structure. However, in the Y268A and R5A mutants considerably larger openings were observed compared with WT LeuT.…”
Section: Tm1a In the Ifo State Shows Smaller Opening In Simulationmentioning
confidence: 99%